Lactoferrin Isolation Using Monolithic Column Coupled with Spectrometric or Micro-Amperometric Detector - Adam, Vojtech; Zitka, Ondrej; Dolezal, Petr; Zeman, Ladislav; Horna, Ales; Hubalek, Jaromir; Sileny, Jan; Krizkova, Sona; Trnkova, Libuse; Kizek, Rene (Sensors (Basel, Switzerland), 2008)
Lactoferrin is a multifunctional protein with antimicrobial activity and others tohealth beneficial properties. The main aim of this work was to propose easy to usetechnique for lactoferrin isolation from cow colostrum samples. Primarily we utilizedsodium dodecyl sulphate - polyacrylamide gel electrophoresis for isolation of lactoferrinfrom the real samples. Moreover we tested automated microfluidic Experionelectrophoresis system to isolate lactoferrin from the collostrum sample. The welldeveloped signal of lactoferrin was determined with detection limit (3 S/N) of 20 ng/ml. Inspite of the fact that Experion is faster than SDS-PAGE both separation techniques cannotbe used in routine analysis. Therefore we have tested third separation technique, ionexchange chromatography, using monolithic column coupled with UV-VIS detector (LCUV-VIS). We optimized wave length (280 nm), ionic strength of the elution solution (1.5M NaCl) and flow rate of the retention and elution solutions (0.25 ml/min and 0.75 ml/min.respectively). Under the optimal conditions the detection limit was estimated as 0.1 μg/mlof lactoferrin measured. Using LC-UV-VIS we determined that lactoferrin concentrationvaried from 0.5 g/l to 1.1 g/l in cow colostrums collected in the certain time interval up to 72 hours after birth. Further we focused on miniaturization of detection device. We testedamperometric detection at carbon electrode. The results encouraged us to attempt tominiaturise whole detection system and to test it on analysis of real samples of humanfaeces, because lactoferrin level in faeces is closely associated with the inflammations ofintestine mucous membrane. For the purpose of miniaturization we employed thetechnology of printed electrodes. The detection limit of lactoferrin was estimated as 10μg/ml measured by the screen-printed electrodes fabricated by us. The fabricatedelectrodes were compared with commercially available ones. It follows from the obtainedresults that the responses measured by commercial electrodes are app. ten times highercompared with those measured by the electrodes fabricated by us. This phenomenonrelates with smaller working electrode surface area of the electrodes fabricated by us(about 50 %) compared to the commercial ones. The screen-printed electrodes fabricatedby us were utilized for determination of lactoferrin faeces. Regarding to fact that sample offaeces was obtained from young and healthy man the amount of lactoferrin in sample wasunder the limit of detection of this method.
Keywords: Linear Sweep Voltammetry; Electrochemistry; Lactoferrin; UV-VIS Spectrometry; Milk Protein; Screen-Printed Carbon Electrode; Monolithic Column; Liquid Chromatography